Mechanical and Wear Studies on AA7075/Nano TiC/Graphite Hybrid Composites for Tribological Applications - Clement Tom Scaria; R. Pugazhenthi; Ajith Arul Daniel; K. Santhosh (Advances in Materials Science and Engineering)
The current paper aims to study wear behaviour of AA7075 reinforced with different weight percentage of nano-TiC and graphite particles under dry sliding condition. TiC particles are taken in different weight percentages (5%, 10%, and 15%), and graphite was chosen as (3%, 4%, and 5%) along with three different levels of sliding speed, applied load, and sliding velocity. The fabrication was conducted using stir casting equipment, and the experiments were done using Taguchi’s L27 orthogonal array. The Taguchi and ANOVA results applied load and percentage of TiC are the most influencing parameters which influences wear loss and friction coefficient